2014
DOI: 10.1002/job.1978
|View full text |Cite
|
Sign up to set email alerts
|

Good acting requires a good cast: A meso-level model of deep acting in work teams

Abstract: Summary This study proposes and tests a meso‐level model of deep acting in work teams that draws on emotional contagion theory to explain how shared means of complying with display rules can arise in work teams. We argue that the presence of influential deep actors can lead to greater convergence (lower dispersion) on individual deep acting in the team. That is, team members behave more similarly. When a team has greater convergence, deep acting by individual members should be related to lower emotional exhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 100 publications
2
32
1
Order By: Relevance
“…On both a collective and an individual level intervention could, for example, encourage employees to use reevaluation as this emotion regulation strategy moderates the effect of emotional dissonance on burnout. In their study, Becker and Cropanzano () suggested that team‐level deep acting effects can foster benefits for team members (lower emotional exhaustion and higher satisfaction) and organizations (higher job performance). Moreover while team collaboration problems appear as an important predictor of burnout among health care professionals (Van Bogaert, Clarke, Vermeyen, Meulemans, & Van de Heyning, ), our study clearly indicated that reflexivity among teams and specially social reflexivity represents a strong social resource.…”
Section: Discussionmentioning
confidence: 99%
“…On both a collective and an individual level intervention could, for example, encourage employees to use reevaluation as this emotion regulation strategy moderates the effect of emotional dissonance on burnout. In their study, Becker and Cropanzano () suggested that team‐level deep acting effects can foster benefits for team members (lower emotional exhaustion and higher satisfaction) and organizations (higher job performance). Moreover while team collaboration problems appear as an important predictor of burnout among health care professionals (Van Bogaert, Clarke, Vermeyen, Meulemans, & Van de Heyning, ), our study clearly indicated that reflexivity among teams and specially social reflexivity represents a strong social resource.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, researchers found that display rules, referred to perceived expectations to display positive emotions and suppressing negative emotions, positively related to burnout (Brotheridge & Grandey, ; Cheung & Tang, ; Kammeyer‐Mueller et al, ). On the other hand, specific emotional regulation strategies such as deep acting (when individuals change their actual experienced emotions to conform to display rules) and surface acting (when individuals fake desired emotions or suppress undesired emotions to meet job requirements) have also been found to positively relate to burnout (Becker & Cropanzano, ; Grandey & Melloy, ; Kammeyer‐Mueller et al, ; Sliter et al, ). In addition, previous research has found that display rules, which tend to be stable within individuals (Xanthopoulou, Bakker, Oerlemans, & Koszucka, ), positively predicted both deep acting and surface acting (Mesmer‐Magnus, DeChurch, & Wax, ), indicating that individuals' perception of display rules can affect how they regulate their emotions at work and is thus likely to affect how they react to emotion‐depleting experiences such as workplace incivility.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…In brief, the literature generally portrays emotional labor theory as a more restricted set of concepts, namely, intrinsic ER strategies used in interpersonal work contexts to achieve organizational emotional display demands (Becker and Cropanzano ; Diefendorff et al . ).…”
Section: Conceptualizing Er At the Individual Levelmentioning
confidence: 99%
“…Some researchers have recognized that emotional labor occurs at multiple levels and can be framed within interpersonal ER (e.g. Ashkanasy and Humphrey ; Becker and Cropanzano ; Côté ; Côté et al . ).…”
Section: Er At the Interpersonal Levelmentioning
confidence: 99%